Capability Reconfiguration: An Analysis Of Incumbent Responses To Technological Change - Lavie, Dovev (Academy of Management Review, 2006)
I present a model of capability reconfiguration, integrating the Schumpeterian perspective on technological discontinuities with the dynamic capabilities literature to explain the responses of incumbents to technological change. I identify substitution, evolution, and transformation as three mechanisms of capability reconfiguration and then link the choice of reconfiguration mechanism to the nature of technological change and to the attributes of capabilities. I conclude that the extent to which the chosen mechanism enables incumbents to overcome cognitive and operational impediments influences their capacity to bridge capability gaps.